Teaching Stress to ESL Students - Hossain, Gazi Shahadat; Tarannum, Sawsan (IIUC Studies, 2012)
In English conversation, people use their voice as a complex instrument. As they use sound systems of their languages, their pronunciation usually produces infinite variations of meaning. This variation made by stress on particular syllable or word creates confusion in the minds of the ESL (English as a Second Language) students in identifying the correct meaning of the word. So it is essential for ESL students to be familiar with English stress pattern. This essay will highlight the meaning and role of stress, the ways of raising awareness among the students and the techniques of teaching it in the classroom. DOI: http://dx.doi.org/10.3329/iiucs.v6i0.12253 IIUC Studies Vol.6 2010: 123-132